Detection of unknown primary tumor in patients presented with brain metastasis by F-18 fluorodeoxyglucose positron emission tomography/computed tomography - Zehra Pınar Koç; Pelin Özcan Kara; Ahmet Dağtekin (CNS Oncology, 2018)
Aim: F-18 fluorodeoxyglucose (FDG) PET/CT has several advantages in diagnosis of cancer of unknown primary with reported incremental diagnostic value. In this study, we evaluated the patients who were presented with multiple brain metastasis and unknown primary tumor. Materials & methods: 31 patients (17 males, 14 females; mean: 56.1 ± 14.22 years old) with diagnosis of brain metastasis according to histopathology and/or MRI were included into this retrospective study. Results: The patients presented with hypermetabolic (n = 17; mean SUVmax: 11.6 ± 6.9) or hypometabolic brain lesions with additional different metastatic sites in 13 patients (mean SUVmax: 9.03 ± 4.02). The primary tumor was determined by FDG PET/CT in 20/26 patients (77%) (lung [n = 6], primary brain [n = 9], renal cell carcinoma [n = 2], skin [n = 1], breast [n = 1] and neuroendocrine tumor [n = 1]). Conclusion: New generation multislice scanners may provide higher detection ratios. The detection rate of FDG PET/CT might be higher than previously reported according to this study.